Bacillus velezensis A2 fermentation exerts a protective effect on renal injury induced by Zearalenone in mice - Wang, Nan (Sci Rep, 2018)
Zearalenone (ZEN) is an estrogen-like mycotoxin occurring in food and feeds, and it can cause oxidative damage and apoptosis in the testis, liver, and kidney. A current concern for researchers is how to reduce the harm it causes to humans and animals. In this study, our aim was to isolate and identify a novel and efficient ZEN-detoxifying strain of bacteria, and we aimed to assess the protective effect of the isolated strain on kidney damage caused by ZEN in mice. Our results indicated that a strain of Bacillus velezensis (B. velezensis), named A2, could completely degrade ZEN (7.45 μg/mL) after three days of incubation at 37 °C in the Luria-Bertani (LB) medium. This fermentation broth of the B. velezensis A2 strain was given to mice. The histopathological analysis indicated that the fermentation broth from the B. velezensis A2 strain reduced the degree of renal injury that is induced by ZEN. Furthermore, it greatly reduced the increase in serum levels of creatinine (CRE), uric acid (UA), and urea nitrogen (BUN) caused by ZEN. In addition, B. velezensis A2 strain also significantly inhibited the increase of malonaldehyde (MDA) content, and reversed the decreases of total superoxide dismutase (T-SOD) and glutathione peroxidase (GSH-Px) activities caused by ZEN. Studies have shown that ZEN is involved in the regulation of mRNA and protein levels of genes involved in the ER stress-induced apoptotic pathway, such as heavy chain binding protein (BIP), C-/-EBP homologous protein (CHOP), cysteine Aspartate-specific protease-12 (Caspase-12), c-Jun N-terminal kinase (JNK), and BCL2-related X protein (Bcl-2 and Bax). However, when mice were administered the fermentation broth of the B. velezensis A2 strain, it significantly reversed the expressions of these genes in their kidney tissue. In conclusion, our results indicate that the newly identified strain of B. velezensis A2, has a protective effect from renal injury induced by ZEN in mice. This strain has a potential application in the detoxification of ZEN in feed and protects animals from ZEN poisoning.